Pelatihan Optimasi Digital melalui Media Sosial sebagai Kiat Bertahan di Masa Pandemi bagi Kelompok UP2K Desa Sembawa Kecamatan Jalaksana - Nurhayati, Neni; Suhendar, Dadang; Purnama, Dendi (Empowerment, 2021)
The UP2K group in tips for surviving the pandemic has not yet optimized digital opportunities through social media. The limited activities cannot be adapted into offline form by optimizing the use of social media. The method used in the implementation of the service is training using technical information presentation and simulation methods as well as mentoring with individual and classical approaches. The implementation of the service will be carried out in November 2021 for 3 (three) days starting from November 15, 2021 to November 17, 2021. From the results of this activity, all participants who are members of the UP2K PKK group responded very well and understood the material presented regarding digital optimization through social media. . Positive changes can be seen after doing this activity. It can be seen from the participants who initially still cannot use social media optimally, can turn into people who are able to use social media optimally and wisely.